(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This study investigates the strength of the connection between (total organic carbon TOC and other measures of water quality, such as biological and chemical oxygen demand BOD5, COD), in the context of water quality in the Shat Al Garaf River, southern Iraq. Over two years, water samples were collected and tested to obtain BOD5, COD, and TOC data. The analysis shows a good correlation between TOC and BOD5 (r = 0.95) and TOC and COD (r = 0.93), facilitating the formulation of predictive equations for calculating BOD5 and COD concentrations derived from TOC measurements. Based on the findings, it seems that total organic carbon (TOC) has the potential to function as a trustworthy indicator for evaluating the water quality of the Shat Al Garaf River, which would allow for improved management and monitoring procedures. the need for more research was significant on the link between TOC and BOD5 to improve the knowledge of freshwater resources management in the field.